2007
DOI: 10.1016/j.ejcts.2007.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Is adhesive paper-tape closure of video assisted thoracoscopic port-sites safe?

Abstract: Video assisted thoracoscopic surgery (VATS) is used in lung surgery for diagnostic, staging, curative and palliative purposes. The port-sites are usually sutured with dissolvable sutures. The use of adhesive paper-tape for port-site closure was assessed by a prospective randomised double-blind control trial comparing sutured to adhesive paper-tape closure. The following outcomes were assessed: incidence of clinically significant pneumothorax, wound healing using the ASEPSIS score, patient's comfort (pain score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(27 citation statements)
references
References 3 publications
0
27
0
Order By: Relevance
“…Five studies evaluated pain post-incisional site closure. 27,29,32,34,35 used for pain evaluation; 2 studies used the Visual Analog Scale (VAS) score, 29,34 whereas a 10-point scale and a 4-point scale were used in 2 studies, 32,35 and 1 study, 27 respectively (Table 2). No study reported significant difference between the compared groups regarding pain perception on follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies evaluated pain post-incisional site closure. 27,29,32,34,35 used for pain evaluation; 2 studies used the Visual Analog Scale (VAS) score, 29,34 whereas a 10-point scale and a 4-point scale were used in 2 studies, 32,35 and 1 study, 27 respectively (Table 2). No study reported significant difference between the compared groups regarding pain perception on follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…After excluding old studies (published before 1990) and those enrolling pediatric patients, a total of 12 studies were included in this metaanalysis. [24][25][26][27][28][29][30][31][32][33][34][35]…”
Section: Selected Studiesmentioning
confidence: 99%
See 3 more Smart Citations